Evolution of transitional structures from puff to slug through multiple splitting in a pipe flow at low Reynolds number - Krauß, Jens; Ertunc, Özgür; Ostwald, Christina; Lienhart, Hermann; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
During laminar-to-turbulent transition in low Reynolds pipe flows, three main types of flow structures occur: traveling waves and the turbulent flow structures, namely puffs and slugs. In the present work, detailed experiments on the probability of occurrence and propagation speed of puffs, splitting puffs and slugs were conducted with the transition pipe-flow facility of LSTM-Erlangen. During the investigations, fully developed laminar pipe flow was triggered by an iris diaphragm with a pre-defined amplitude and lapse time. Different types of single and multiple puffs are classified and the probability of their occurrence as well as their propagation speed at the end of pipes with different lengths are evaluated.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.evolut_4